Brodalumab: 5-Year US Pharmacovigilance Report - Mark G. Lebwohl; John Y. Koo; April W. Armstrong; Bruce E. Strober; George M. Martin; Nicole N. Rawnsley; Earl L. Goehring; Abby A. Jacobson (Adis, Springer Healthcare, 2024)
Abstract Introduction Brodalumab is a human interleukin-17 receptor A antagonist indicated for the treatment of moderate-to-severe plaque psoriasis in adult patients who are candidates for systemic therapy or phototherapy and have failed to respond or have lost response to other systemic therapies. Although the US prescribing information for brodalumab includes a boxed warning regarding suicidal ideation and behavior, no causal association has been demonstrated. Here, we summarize 5 years of pharmacovigilance data, from August 15, 2017, through August 14, 2022, reported to Ortho Dermatologics by US patients and healthcare providers. Methods Prevalence of the most common adverse events (AEs) listed in the brodalumab package insert (incidence ≥ 1%) and AEs of special interest are described. Brodalumab exposure was estimated as the time from the first to last prescription-dispensing authorization dates. Data were collected from 4744 patients in the USA, with an estimated exposure of 5815 patient-years. Results Over 5 years, 11 cases of adjudicated major adverse cardiovascular events were reported (0.23 events/100 patients), a rate lower than that experienced by patients in the international Psoriasis Longitudinal Assessment and Registry. There were 106 serious infections. No serious fungal infections were reported. There were 40 confirmed and 2 suspected COVID-19 cases, with no new COVID-19-related deaths. Of 49 reported malignancies among 42 patients, 3 were deemed possibly related to brodalumab. No completed suicides and no new suicidal attempts were reported. Conclusion Five-year pharmacovigilance data are consistent with the established safety profile reported in long-term clinical trials and previous pharmacovigilance reports, with no new safety signals.